Youth and the State in Guinea: Meandering Lives - Engeler, Michelle (transcript, 2019)
By combining an ethnographic study of youth with an analysis of the local state in the making, this research monograph introduces the perspective of »meandering lives« to grasp being young and growing up in the Guéckédou borderland, a remote space approximately 700 kilometers southeast of Conakry, Guinea's capital. This history-sensitive perspective represents a fruitful lens to not only depict youth but to also draw a nuanced picture of the functioning of the state in Guinea.